To solve for A in the equation \( A = 5 - \frac{11}{3} \), we should first simplify the expression on the right side.
Start by converting 5 into a fraction with a denominator of 3:
\[ 5 = \frac{15}{3} \]
Now, perform the subtraction:
\[ A = \frac{15}{3} - \frac{11}{3} = \frac{15 - 11}{3} = \frac{4}{3} \]
Now let's evaluate the given options to see which one is equivalent to \( \frac{4}{3} \):
-
A = \(-\frac{2}{3} + \frac{1}{3}\)
\( -\frac{2}{3} + \frac{1}{3} = -\frac{2 - 1}{3} = -\frac{1}{3} \) (not equal to \( \frac{4}{3} \)) -
A = \(\frac{12}{3} - \frac{1}{3}\)
\( \frac{12}{3} - \frac{1}{3} = \frac{12 - 1}{3} = \frac{11}{3} \) (not equal to \( \frac{4}{3} \)) -
A = \(\frac{15}{3} + \frac{1}{3}\)
\( \frac{15}{3} + \frac{1}{3} = \frac{15 + 1}{3} = \frac{16}{3} \) (not equal to \( \frac{4}{3} \)) -
A = \(\frac{12}{3} + \frac{1}{3}\)
\( \frac{12}{3} + \frac{1}{3} = \frac{12 + 1}{3} = \frac{13}{3} \) (not equal to \( \frac{4}{3} \))
None of the expressions provided appear to equal \( \frac{4}{3} \). If there is a mistake in parsing the question or the options provided, please clarify so I can assist you better!